2005
DOI: 10.1007/s00268-005-7759-3
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Oriental Primary Intrahepatic Lithiasis: Experience with 48 Cases

Abstract: Abstract. An experience with the diagnosis and treatment of patients with non-Oriental primary intrahepatic lithiasis (PIHL) is described. A group of 48 native Brazilian patients with symptomatic PIHL were studied, and the patientsÕ characteristics, diagnoses, treatment protocols based on the presentation of the disease, prognostic factors, and late results were analyzed. Liver resection was performed in patients with an irreversible lesion, such as parenchymal atrophy or biliary stenosis; and biliary drainage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…Hepatolithiasis has been defined as the occurrence of stones in any intrahepatic bile duct proximal to the confluence of the right and left hepatic ducts, irrespective of the presence of stones in the main bile duct or the gallbladder 1 . It is prevalent in Japan and Southeast Asia 2 and uncommon in Western countries 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…Hepatolithiasis has been defined as the occurrence of stones in any intrahepatic bile duct proximal to the confluence of the right and left hepatic ducts, irrespective of the presence of stones in the main bile duct or the gallbladder 1 . It is prevalent in Japan and Southeast Asia 2 and uncommon in Western countries 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the literature reports the risk of development of cancer in patients with intrahepatic lithiasis at 5.8 to 17% [17][18][19]. For this reason, liver resection has been increasingly used as a treatment for PIHL [4,5,7,[20][21][22]. Mabrut et al [4] recently reported the results of a multicenter study in which 27 patients underwent liver resection for localized disease with satisfactory results in 87% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Primary stone formation must be distinguished from gallstones due to stone migration from the gallbladder and from stone formation upstream from post-operative biliary strictures. PIHL is a very rare condition in Western countries (less than 1% of all gallstones) [4], but is more common in the Orient (about 4% of gallstones in Japan) [5]. Bile stasis and stone formation on the one hand and chronic inflammation and infection on the other result in progressive atrophy of the involved parenchyma and lead to dysplastic transformation of the biliary epithelium, which may result in the development of cholangiocarcinoma [6].…”
Section: Introductionmentioning
confidence: 99%
“…In secondary intrahepatic lithiasis, stones are originally formed in the gallbladder or common bile duct and then migrate to the liver. Intrahepatic lithiasis is more common in the left lobe possibly because an acute angle between the common hepatic duct and the left hepatic duct which could induce bile stasis 2 , 5 , 13 , 17 .…”
Section: Introductionmentioning
confidence: 99%